Analisis Implementasi Aplikasi Kasir Pada UMKM Di Kota Singkawang - Raine Apriliani Budi; Ali Afif; Febriati Febriati (Jurnal Akuntansi, Auditing dan Investasi, 2025)
This research prioritizes discussing the implementation of the cashier application in UMKM in Singkawang City which aims to find out how the use of the cashier application is implemented and the factors that support decision making in using the cashier application. This research uses qualitative research methods with data collection used, namely observation, interviews and documentation. The data analysis techniques used are descriptions of observation results, flowcharts, detailed interviews. Based on the results of this research, in implementing the cashier application, sales activities are more effective and efficient because it makes it easier to carry out the process of recording goods price lists, inputting orders and carrying out transactions with customers. Sales reports that can be viewed in real time can provide more benefits than conventional cash register functions in general because they can combine several jobs into one system and can minimize errors that occur during data processing. And the factors that support the decision to use a cashier application can be influenced by internal and external factors.